Promoting individual and community health at the library - Flaherty, Mary Grace (Chicago : ALA Editions, 2018)
Flaherty covers strategies used by libraries to improve people's access to and use of health information. Whether for an individual, a library program, or a community program, it is important to provide health information and sources that are not outdated, difficult to retain, or misrepresented. Public libraries are the perfect setting for empowering patrons with this information.
Public libraries and consumer health: a historic perspective -- Health information provision in public libraries -- Health programming in public libraries -- Reaching out to the community: opportunities for wider engagement -- Looking ahead: future opportunities -- Onward and upward.
Includes bibliographical references and index.
Keywords: Health Education; Health Literacy; Health Promotion